Public health and international drug policy - Csete, Joanne; Kamarulzaman, Adeeba; Kazatchkine, Michel; Altice, Frederick; Balicki, Marek; Buxton, Julia; Cepeda, Javier; Comfort, Megan; Goosby, Eric; Goulão, João; Hart, Carl; Kerr, Thomas; et al. (Lancet (London, England), 2016)
UNLABELLED: In September 2015, the member states of the United Nations endorsed sustainable development goals (SDG) for 2030 that aspire to human rights-centered approaches to ensuring the health and well-being of all people. The SDGs embody both the UN Charter values of rights and justice for all and the responsibility of states to rely on the best scientific evidence as they seek to better humankind. In April 2016, these same states will consider control of illicit drugs, an area of social policy that has been fraught with controversy, seen as inconsistent with human rights norms, and for which scientific evidence and public health approaches have arguably played too limited a role. The previous UN General Assembly Special Session (UNGASS) on drugs in 1998 – convened under the theme “a drug-free world, we can do it!” – endorsed drug control policies based on the goal of prohibiting all use, possession, production, and trafficking of illicit drugs. This goal is enshrined in national law in many countries. In pronouncing drugs a “grave threat to the health and well-being of all mankind,” the 1998 UNGASS echoed the foundational 1961 convention of the international drug control regime, which justified eliminating the “evil” of drugs in the name of “the health and welfare of mankind.” But neither of these international agreements refers to the ways in which pursuing drug prohibition itself might affect public health. The “war on drugs” and “zero-tolerance” policies that grew out of the prohibitionist consensus are now being challenged on multiple fronts, including their health, human rights, and development impact. The Johns Hopkins – Lancet Commission on Drug Policy and Health has sought to examine the emerging scientific evidence on public health issues arising from drug control policy and to inform and encourage a central focus on public health evidence and outcomes in drug policy debates, such as the important deliberations of the 2016 UNGASS on drugs. The Johns Hopkins-Lancet Commission is concerned that drug policies are often colored by ideas about drug use and drug dependence that are not scientifically grounded. The 1998 UNGASS declaration, for example, like the UN drug conventions and many national drug laws, does not distinguish between drug use and drug abuse. A 2015 report by the UN High Commissioner for Human Rights, by contrast, found it important to emphasize that “[d]rug use is neither a medical condition nor does it necessarily lead to drug dependence.” The idea that all drug use is dangerous and evil has led to enforcement-heavy policies and has made it difficult to see potentially dangerous drugs in the same light as potentially dangerous foods, tobacco, alcohol for which the goal of social policy is to reduce potential harms. HEALTH IMPACT OF DRUG POLICY BASED ON ENFORCEMENT OF PROHIBITION: The pursuit of drug prohibition has generated a parallel economy run by criminal networks. Both these networks, which resort to violence to protect their markets, and the police and sometimes military or paramilitary forces that pursue them contribute to violence and insecurity in communities affected by drug transit and sales. In Mexico, the dramatic increase in homicides since the government decided to use military forces against drug traffickers in 2006 has been so great that it reduced life expectancy in the country. Injection of drugs with contaminated equipment is a well-known route of HIV exposure and viral hepatitis transmission. People who inject drugs (PWID) are also at high risk of tuberculosis. The continued spread of unsafe injection-linked HIV contrasts the progress that has been seen in reducing sexual and vertical transmission of HIV in the last three decades. The Commission found that that repressive drug policing greatly contributes to the risk of HIV linked to injection. Policing may be a direct barrier to services such as needle and syringe programmes (NSP) and use of non-injected opioids to treat dependence among those who inject opioids, known as opioid substitution therapy (OST). Police seeking to boost arrest totals have been found to target facilities that provide these services to find, harass, and detain large numbers of people who use drugs. Drug paraphernalia laws that prohibit possession of injecting equipment lead PWID to fear carrying syringes and force them to share equipment or dispose of it unsafely. Policing practices undertaken in the name of the public good have demonstrably worsened public health outcomes. Amongst the most significant impacts of pursuit of drug prohibition identified by the Commission with respect to infectious disease is the excessive use of incarceration as a drug-control measure. Many national laws impose lengthy custodial sentences for minor, non-violent drug offenses; people who use drugs (PWUD) are over-represented in prison and pretrial detention. Drug use and drug injection occur in prisons, though their occurrence is often denied by officials. HIV and hepatitis C virus (HCV) transmission occurs among prisoners and detainees, often complicated by co-infection with TB and in many places multidrug-resistant TB, and too few states offer prevention or treatment services in spite of international guidelines that urge comprehensive measures, including provision of injection equipment, for people in state custody. Mathematical modelling undertaken by the Commission illustrates that incarceration and high HCV risk in the post-incarceration period can contribute importantly to national HCV incidence amongst PWID in a range of countries with varying levels of incarceration, different average prison sentences, durations of injection, and OST coverage levels in prison and following release. For example, in Thailand where PWID may spend nearly half their injection careers in prison, an estimated 63% of incident HCV infection could occur in prison. In Scotland, where prison sentences are shorter for PWUD and OST coverage is relatively high in prison, an estimated 54% of incident HCV infection occurs in prison, but as much as 21% may occur in the high-risk post-release period. These results underscore the importance of alternatives to prison for minor drug offences, ensuring access to OST in prison, and a seamless link from prison services to OST in the community. The evidence also clearly demonstrates that drug law enforcement has been applied in a discriminatory way against racial and ethnic minorities in a number of countries. The US is perhaps the best documented but not the only case of racial biases in policing, arrest, and sentencing. In 2014, African American men were more than five times more likely than whites to be incarcerated in their lifetime, though there is no significant difference in rates of drug use among these populations. The impact of this bias on communities of people of color is inter-generational and socially and economically devastating. The Commission also found significant gender biases in current drug policies. Of women in prison and pretrial detention around the world, a higher percentage are detained because of drug infractions than is the case for men. Women involved in drug markets are often on the bottom rungs – as couriers or drivers – and may not have information about major traffickers to trade as leverage with prosecutors. Gender and racial biases have marked overlap, making this an intersectional threat to women of color, their children, families, and communities. In both prison and the community, HIV, HCV and TB programmes for PWUD – including testing, prevention and treatment – are gravely underfunded at the cost of preventable death and disease. In a number of middle-income countries where large numbers of PWUD live, HIV and TB programmes for PWUD that were expanded with support from the Global Fund to Fight AIDS, TB and Malaria have lost funding due to changes in the Fund’s eligibility criteria. There is an unfortunate failure to emulate the example of Western European countries that have eliminated unsafe injection-linked HIV as a public health problem by sustainably scaling up prevention and care and enabling minor offenders to avert prison. Political resistance to harm reduction measures dismisses strong evidence of their effectiveness and cost-effectiveness. Mathematical modeling shows that if OST, NSP and antiretroviral therapy for HIV are all available, even if the coverage of each of them is not over 50%, their synergy can lead to effective prevention in a foreseeable future. PWUD are often not seen to be worthy of costly treatments, or they are thought not to be able to adhere to treatment regimens in spite of evidence to the contrary. Lethal drug overdose is an important public health problem, particularly in light of rising consumption of heroin and prescription opioids in some parts of the world. Yet the Commission found that the pursuit of drug prohibition can contribute to overdose risks in numerous ways. It creates unregulated illegal markets in which it is impossible to control adulterants of street drugs that add to overdose risk. Several studies also link aggressive policing to rushed injection and overdose risk. People with a history of drug use, over-represented in prison because of prohibitionist policies, are at extremely high risk of overdose when released from state custody. Lack of ready access to OST also contributes to injection of opioids, and bans on supervised injection sites cut off an intervention that has proven very effective in reducing overdose deaths. Restrictive drug policies also contribute to unnecessary controls on naloxone, a medicine that can reverse overdose very effectively. Though a small percentage of PWUD will ever need treatment for drug dependence, that minority faces enormous barriers to humane and affordable treatment in many countries. There are often no national standards for quality of drug dependence treatment and no regular monitoring of practices. In too many countries, beatings, forced labor, and denial of health care and adequate sanitation are offered in the name of treatment, including in compulsory detention centres that are more like prisons than treatment facilities. Where there are humane treatment options, it is often the case that those most in need of it cannot afford it. In many countries, there is no treatment designed particularly for women, though it is known that women’s motivations for and physiological reactions to drug use differ from those of men. The pursuit of the elimination of drugs has led to aggressive and harmful practices targeting people who grow crops used in the manufacture of drugs, especially coca leaf, opium poppy, and cannabis. Aerial spraying of coca fields in the Andes with the defoliant glyphosate (N-(phosphonomethyl glycine) has been associated with respiratory and dermatological disorders and with miscarriages. Forced displacement of poor rural families who have no secure land tenure exacerbates their poverty and food insecurity and in some cases forces them to move their cultivation to more marginal land. Geographic isolation makes it difficult for state authorities to reach drug crop cultivators in public health and education campaigns and it cuts cultivators off from basic health services. Alternative development programmes meant to offer other livelihood opportunities have poor records and have rarely been conceived, implemented, or evaluated with respect to their impact on people’s health. Research on drugs and drug policy has suffered from the lack of a diversified funding base and assumptions about drug use and drug pathologies on the part of the dominant funder, the US government. At a time when drug policy discussions are opening up around the world, there is an urgent to bring the best of non-ideologically-driven health science, social science and policy analysis to the study of drugs and the potential for policy reform. POLICY ALTERNATIVES IN REAL LIFE: Concrete experiences from many countries that have modified or rejected prohibitionist approaches in their response to drugs can inform discussions of drug policy reform. A number of countries, such as Portugal and the Czech Republic, decriminalised minor drug offenses years ago, with significant savings of money, less incarceration, significant public health benefits, and no significant increase in drug use. Decriminalisation of minor offenses along with scaling up low-threshold HIV prevention services enabled Portugal to control an explosive unsafe injection-linked HIV epidemic and likely enabled the Czech Republic to prevent one from happening. Where formal decriminalisation may not be an immediate possibility, scaling up health services for PWUD can demonstrate the value to society of responding with support rather than punishment to people who commit minor drug infractions. A pioneering OST program in Tanzania is encouraging communities and officials to consider non-criminal responses to heroin injection. In Switzerland and the city of Vancouver, Canada, dramatic improvements in access to comprehensive harm reduction services, including supervised injection sites and heroin-assisted treatment, transformed the health picture for PWUD. Vancouver’s experience also illustrates the importance of meaningful participation of PWUD in decision-making on policies and programmes affecting their communities. CONCLUSIONS AND RECOMMENDATIONS: Policies meant to prohibit or greatly suppress drugs present a paradox. They are portrayed and defended vigorously by many policy-makers as necessary to preserve public health and safety, and yet the evidence suggests they have contributed directly and indirectly to lethal violence, communicable disease transmission, discrimination, forced displacement, unnecessary physical pain, and the undermining of people’s right to health. Some would argue that the threat of drugs to society may justify some level of abrogation of human rights for protection of collective security, as is also foreseen by human rights law in case of emergencies. International human rights standards dictate that in such cases, societies still must choose the least harmful way to address the emergency and that emergency measures must be proportionate and designed specifically to meet transparently defined and realistic goals. The pursuit of drug prohibition meets none of these criteria. Standard public health and scientific approaches that should be part of policy-making on drugs have been rejected in the pursuit of prohibition. The idea of reducing the harm of many kinds of human behavior is central to public policy in the areas of traffic safety, tobacco and alcohol regulation, food safety, safety in sports and recreation, and many other areas of human life where the behavior in question is not prohibited. But explicitly seeking to reduce drug-related harms through policy and programmes and to balance prohibition with harm reduction is regularly resisted in drug control. The persistence of unsafe injection-linked HIV and HCV transmission that could be stopped with proven, cost-effective measures remains one of the great failures of the global responses to these diseases. Drug policy that is dismissive of extensive evidence of its own negative impact and of approaches that could improve health outcomes is bad for all concerned. Countries have failed to recognise and correct the health and human rights harms that pursuit of prohibition and drug suppression have caused and in so doing neglect their legal responsibilities. They readily incarcerate people for minor offenses but then neglect their duty to provide health services in custodial settings. They recognize uncontrolled illegal markets as the consequence of their policies, but they do little to protect people from toxic, adulterated drugs that are inevitable in illegal markets or the violence of organized criminals, often made worse by policing. They waste public resources on policies that do not demonstrably impede the functioning of drug markets, and they miss opportunities to invest public resources wisely in proven health services for people often too frightened to seek services. To move toward the balanced policy that UN member states have called for, we offer the following recommendations: Decriminalisation: Decriminalise minor, non-violent drug offenses – use, possession, and petty sale – and strengthen health and social-sector alternatives to criminal sanctions. Reducing violence and discrimination in policing: Reduce the violence and other harms of drug policing, including phasing out the use of military forces in drug policing, better targeting of policing on the most violent armed criminals, allowing possession of syringes, not targeting harm reduction services to boost arrest totals, and eliminating racial and ethnic discrimination in policing. Reducing harms: Ensure easy access for all who need them to harm reduction services as a part of responding to drugs, recognizing the effectiveness and cost-effectiveness of scaling up and sustaining these services. OST, NSP, supervised injection sites, and access to naloxone – brought to a scale adequate to meet demand – should all figure in health services and should include meaningful participation of PWUD in planning and implementation. Harm reduction services are crucial in prison and pretrial detention and should be scaled up in these settings. The 2016 UNGASS should do better than the UN Commission on Narcotic Drugs (CND) in naming harm reduction explicitly and endorsing its centrality to drug policy. Treatment and care for PWUD: Prioritize PWUD in treatment for HIV, HCV, TB, and ensure that services are adequate to ensure access for all who need care. Ensure availability of humane and scientifically sound treatment for drug dependence, including scaled-up OST in the community as well as in prisons, rejecting compulsory detention and abuse in the name of treatment. Access to controlled medicines: Ensure access to controlled medicines, establishing inter-sectoral national authorities to determine levels of need and giving the World Health Organization (WHO) the resources to assist the International Narcotics Control Board (INCB) in using the best science to determine the level of need for controlled medicines in all countries. Gender-responsive policies: Reduce the negative impact of drug policy and law on women and their families, especially minimizing custodial sentences for women who commit non-violent offenses and developing appropriate health and social support, including gender-appropriate treatment of drug dependence, for those who need it. Crop production: Efforts to address drug crop production must take health into account. Aerial spraying of toxic herbicides should be stopped, and alternative development programmes should be part of integrated development strategies, developed and implemented in meaningful consultation with the people affected. Improve research: There is a need for a more diverse donor base to fund the best new science on drug policy experiences in a non-ideological way that, among other things, interrogates and moves beyond the excessive pathologising of drug use. UN governance of drug control: UN governance of drug policy must be improved, including by respecting WHO’s authority to determine the dangerousness of drugs. Countries should be urged to include high-level health officials in their delegations to CND. Improved representation of health officials in national delegations to CND would, in turn, be a likely result of giving health authorities an important day-to-day role in multi-sectoral national drug policy-making bodies. Better metrics: Health, development, and human rights indicators should be included in metrics to judge success of drug policy; WHO and UNDP should help formulate them. UNDP has already suggested that indicators such as access to treatment, rate of overdose deaths, and access to social welfare programmes for people who use drugs would be useful indicators. All drug policies should also be monitored and evaluated as to their impact on racial and ethnic minorities, women, children and young people, and people living in poverty. Scientific approach to regulated markets: Move gradually toward regulated drug markets and apply the scientific method to their evaluation. While regulated legal drug markets are not politically possible in the short term in some places, the harms of criminal markets and other consequences of prohibition catalogued in this report are likely to lead more countries (and more US states) to move gradually in that direction, a direction we endorse. As those decisions are taken, we urge governments and researchers to apply the scientific method and ensure independent, multidisciplinary and rigorous evaluation of regulated markets to draw lessons and inform improvements in regulatory practices, and to continue evaluating and improving. We urge health professionals in all countries to inform themselves and join debates on drug policy at all levels. True to the stated goals of the international drug control regime, it is possible to have drug policy that contributes to the health and well-being of humankind, but not without bringing to bear the evidence of the health sciences and the voices of health professionals.
Keywords: Substance Abuse Treatment Centers; řízení společenských procesů; veřejné zdravotnictví; Risk-Taking; Health Services Accessibility; kontaminace zdravotnického vybavení; HIV Infections; dostupnost zdravotnických služeb; centra pro terapii drogových závislostí; Equipment Contamination; Internationality; lidé; prosazení zákonů; Law Enforcement; kongresy jako téma; internacionalita; Organizace spojených národů; virová hepatitida u lidí; HIV infekce; Public Health; Congresses as Topic; Hepatitis, Viral, Human; Substance-Related Disorders; kontrola léčiv a omamných látek; poruchy spojené s užíváním psychoaktivních látek; riskování; Social Control Policies; United Nations; Drug and Narcotic Control; Humans